2018
DOI: 10.1088/1361-6560/aabeda
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight PET time calibration using data consistency

Abstract: This paper presents new data driven methods for the time of flight (TOF) calibration of positron emission tomography (PET) scanners. These methods are derived from the consistency condition for TOF PET, they can be applied to data measured with an arbitrary tracer distribution and are numerically efficient because they do not require a preliminary image reconstruction from the non-TOF data. Two-dimensional simulations are presented for one of the methods, which only involves the two first moments of the data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Even with our measured CTRs in the range of few hundreds of picoseconds FWHM, a range easily achieved nowadays, other sources of time offsets were important to take into account, such as the radioactive source exact position, SiPM delays and missed annihilation photon travel time when using side irradiation. There are already extensive works on time calibration in the context of TOF-PET to compensate for possible delays essentially due to SiPMs (Defrise et al 2018, Li 2019. Controlling very precisely all the possible time offsets that could impact the accuracy of the signal time-stamping process in a scanner is paramount to reach ultra-fast timing in the range of tens of picoseconds for TOF-PET.…”
Section: Discussionmentioning
confidence: 99%
“…Even with our measured CTRs in the range of few hundreds of picoseconds FWHM, a range easily achieved nowadays, other sources of time offsets were important to take into account, such as the radioactive source exact position, SiPM delays and missed annihilation photon travel time when using side irradiation. There are already extensive works on time calibration in the context of TOF-PET to compensate for possible delays essentially due to SiPMs (Defrise et al 2018, Li 2019. Controlling very precisely all the possible time offsets that could impact the accuracy of the signal time-stamping process in a scanner is paramount to reach ultra-fast timing in the range of tens of picoseconds for TOF-PET.…”
Section: Discussionmentioning
confidence: 99%
“…To finish this Section, recent work has indicated that MLAA can be sensitive to errors in the system modeling including timing calibration. Methods to compensate for this are still under development …”
Section: Past and Present Attenuation Estimation Methodsmentioning
confidence: 99%
“…Based on linear fitting in logarithmic scales, the RMS errors with and without scatter were respectively proportional to N −0.520 and N −0.497 , with N denotes the total number of true events. The numerical method has the similar noise behavior to the method using integral equation (Defrise et al 2018).…”
Section: Timing Offsets Estimated From Noisy Datamentioning
confidence: 97%
“…Inspired by the paper (Werner and Karp 2013) and the recent works Aykac 2017, Rezaei et al 2017), we attempted to tackle the timing calibration problem using TOF data consistency. Most recently, Defrise et al (2018) presented a time calibration method using data consistency for 2-D TOF PET, and timing offsets can be computed by solving an integral equation. Since 3-D PET geometry is open along the axial direction, the method cannot be extended to 3-D (all current clinical PET scanners are operated in 3-D acquisition mode).…”
Section: Introductionmentioning
confidence: 99%